TREATMENT OF SEVERE CASES OF CORONAVIRUS WITH STEM CELLS - Sayfullayeva Feruzabonu (Educational Research in Universal Sciences, 2022)
Coronavirus disease 2019 (COVID-19) has become a global pandemic and has caused diverse clinical statuses ranging from asymptomatic carriers and mild upper respiratory tract symptoms, to severe acute respiratory distress syndrome.The following article is devoted to the treatment of severe cases of coronavirus with stem cells.